2018
DOI: 10.1038/s41393-017-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for pressure ulcers: a summary of evidence for prevention and treatment

Abstract: The effects of most interventions for preventing and treating pressure ulcers in people with spinal cord injury are highly uncertain. Existing evaluations of pressure ulcer interventions include very few participants with spinal cord injury. Subsequently, there is still a need for high-quality randomised trials of such interventions in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 98 publications
(115 reference statements)
0
21
0
4
Order By: Relevance
“…37,38 Although most hospitals subscribe to nursing practices and prophylactic interventions aimed at reducing PUs, a recent Cochrane systematic review concluded that the effects of most of these practices in SCI patients are highly uncertain. 39 As such, prospective randomized-controlled trials investigating the role of modifiable patient behaviors and preventative measures to decrease the risk of PU development in patients with SCI are needed.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Although most hospitals subscribe to nursing practices and prophylactic interventions aimed at reducing PUs, a recent Cochrane systematic review concluded that the effects of most of these practices in SCI patients are highly uncertain. 39 As such, prospective randomized-controlled trials investigating the role of modifiable patient behaviors and preventative measures to decrease the risk of PU development in patients with SCI are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, wound care has received a lot of attention from researchers. Many studies have aimed to investigate which interventions might be effective in promoting wound healing or preventing wounds (Atkinson & Cullum, ; Dumville, Owens, Crosbie, Peinemann, & Liu, ; Lavallée, Gray, Dumville, Russell, & Cullum, ; Norman et al., ; Westby, Norman, Dumville, Stubbs, & Cullum, ). However, less has been written about the basic nature of wounds and their prevalence (Cullum et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In the electrical stimulation group, a 63% and 43% reduction in the surface of the ulcers was seen in comparison to the ultrasound group (p <0.04) 10 Shahrokhi A et al, 2014…”
Section: Shahrokhi a Ghorbanimentioning
confidence: 94%